Transformasi Perilaku Hidup Bersih dan Sehat (PHBS) Melalui Komunikasi Kesehatan Partisipatif Berbasis Media Edukasi Kreatif di Sekolah Dasar - Intan Kumalasari; Hendawati Hendawati; Ayu Febri Wulanda; Agitha Pramury; Ririn Agustina; Maia Anis Salsabila; Nafidzah Shabrina; Marshella Rui Utami; Rindi Antika; Silvy Fitria; Herawati Jaya (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
This study aims to increase the knowledge and awareness of fifth-grade students of SDN 70 Palembang regarding Clean and Healthy Living Behavior (PHBS) through health communication and community empowerment activities. The method used was qualitative research with an interactive approach, which included counseling, demonstrations of six-step handwashing practices, and the use of educational media in the form of banners and leaflets. The results showed a significant increase in students' understanding of PHBS indicators, especially correct handwashing skills and the ability to recognize healthy snacks. Students' enthusiasm in participating in simulations and educational quizzes demonstrated the success of the participatory communication approach. This activity successfully strengthened the role of schools and community health centers in creating a healthier educational environment, by involving students as agents of behavior change. Through this activity, it is hoped that students will be more aware of the importance of maintaining personal and environmental hygiene, and can apply PHBS in their daily lives.